ANALISIS PROSPEK USAHA IKAN HIAS BETTA FISH TIMUR DI KOTA TIMIKA - Brithney Marsyuella Talahatu; Rosdiana (CV. Adiba Aisha Amira, 2025)
This study aims to analyse the prospects of the ornamental fish business, especially betta fish, through a case study of Betta Fish Timur in Timika City. Betta fish farming oflers economic advantages due to its easy maintenance and high market demand. This study uses a qualitative and quantitative descriptive approach with SWOT analysis tools, as well as data collection techniques in the form of questionnaires, observations, interviews, and documentation. The results of the SWOT analysis show that the Betta Fish Timur ornamental fish business has promising prospects thanks to its superior product quality, eflective marketing strategy, and strategic business location. However, challenges such as a shortage of skilled labour and rising feed costs must be overcome. It is recommended that the company improve human resource training, water quality management, and implement innovative marketing strategies.